PREVALENCE OF CRYPTOSPORIDIUM SPP. AMONG ASYMPTOMATIC HEALTHY EXPATRIATE WORKERS IN SHARJAH, UNITED ARAB EMIRATES - ElBakri, Ali; Mogane, Lazarus; Ezzedine, Sinda; Potgieter, Natasha; Bessong, Pascal; AbuOdeh, Raed; Samie, Amidou (African Journal of Infectious Diseases (AJID), 2018)
Background: Epidemiological data on Cryptosporidium infections in the United Arab Emirates (UAE) is scarce.Therefore, the main objective of this study was to determine the prevalence of Cryptosporidium species among acommunity of expatriates in Sharjah, UAE working in different sectors, including the food industry, house maids andother domestic occupations.Materials and Methods: One hundred and thirty four stool samples were collected from asymptomatic individualspresenting to the Sharjah Municipality Public Health Clinic (SMPHC) for screening of intestinal parasites for workpermission purposes between 2009 and 2011. Demographic information such as age, sex, and country of origin wascollected. Genomic DNA extracted from the stool samples were tested for Cryptosporidium species using real-timePCR (qPCR).Results: Twenty-six individuals (19.4%) were positive for Cryptosporidium sp. by PCR. The infection rate was foundto be highest in Afghan nationals (33%; 3/9) compared with the rest of the study population; yet, no significantassociation existed between nationality and infection rate. Moreover, no association was observed between infectionrate and gender (χ2 = 2.439; P = 0.118), nor infection rate and age group (χ2 = 1.219; P = 0.544).Conclusion: Infection by Cryptosporidium sp. was common in the study group, and further studies are needed withinthe native Emirati population before any conclusions can be made about foreigners potentially transmitting the parasite.Furthermore, data provided in this study could help determine its public and veterinary significance particularly inoutbreaks in the country.